Diseño técnico de un parque con hidrogeneración en la parroquia rural Taigue-Esmeraldas - Alcivar Sosa, Lissette Anabela (2023)
Hydropower is a proven and reliable technology that has proven itself in various regions of the world. The ability to convert the constant flow of water in rivers and streams into electricity has been critical in driving sustainable development in rural areas and areas far from conventional energy sources. In the rural parish, the objective of the hydrogeneration project is to implement a sustainable and renewable energy solution. Electricity will be produced through turbines and generators using the local water resource, reducing emissions and protecting the environment. A reliable power supply, economic growth and environmental protection will benefit the community. A feasibility study must be carried out that involves the community, assesses the environmental effects and determines the priority between efficiency and safety. The success of the project and its contribution to the integral development of the rural parish will depend on education and innovation............